A FLORISTIC SURVEY OF FERNS AND LYCOPHYTES ASSOCIATED WITH SEMI-DECIDUOUS FOREST REMNANTS IN SOUTHERN BRAZIL - Lehn, Carlos R.; Arana, Marcelo D.; Bueno, Marcelo L.; Bianchini, Edmilson (Darwiniana, 2018)
The richness of ferns and lycophytes associated with the semi-deciduous forests of southern Brazil remains poorly known. Addressing this situation, the richness of lycophytes and ferns in 11 semi-deciduous forest remnants, located in the northwestern region of Rio Grande do Sul State, Brazil, is presented. In total, four species of lycophytes (two families and two genera) and 88 species of ferns (15 families and 44 genera) were recorded. The most diverse families were Pteridaceae and Polypodiaceae, with 18 and 17 species respectively; Asplenium (10 spp.) was the most diverse genus. Among the recorded species, only Dicksonia sellowiana is cited in the Brazilian List of Threatened Plant Species. Most of the surveyed species have a broad distribution, occurring in South America (44.6%) and Tropical America (32.6%). The surveyed remnants showed intermediate species richness in relation to other areas previously studied in the state of Rio Grande do Sul, except for Parque Estadual do Turvo, where 81 species were recorded. The floristic similarity analysis shows that the Parque Estadual do Turvo is the most dissimilar area, presenting a high number (28) of exclusive species. The observed high value of the cophenetic correlation coefficient (0.968), indicate a small distortion between the similarity matrix and multidimensional space shown in the dendrogram. The present study constitutes an important contribution to the knowledge of the richness of ferns and lycophytes occurring in semi-deciduous forests in southern Brazil. La riqueza de helechos y licofitas asociada a los bosques semi-deciduos del sur de Brasil permanece pobremente conocida. Atendiendo a esta situación, se presenta la riqueza de licofitas y helechos en 11 remanentes de bosque semi-deciduo localizados en la región noroeste del estado de Rio Grande do Sul, Brasil. En total, se registraron cuatro especies de licofitas (dos familias y dos géneros) y 88 especies de helechos (15 familias y 44 géneros). Las familias más diversas fueron Pteridaceae y Polypodiaceae (con 18 y 17 especies respectivamente), siendo Asplenium (10 especies) el género más diverso. Entre las especies registradas, sólo Dicksonia sellowiana está citada en la Lista Brasileña de Especies de Plantas Amenazadas. La mayoría de las especies relevadas poseen una distribución amplia, abarcando Sudamérica (44,6%) y América tropical (32,6%). Los remanentes relevados mostraron una riqueza específica intermedia en relación con otras áreas estudiadas previamente en el estado de Rio Grande do Sul, con la excepción del parque Estadual do Turvo, donde se registraron 81 especies. El análisis de similitud florística demuestra que el Parque Estadual do Turvo es el área más disímil, presentando un alto número (28) de especies exclusivas. El alto valor observado para el coeficiente de correlación cofenética (0.968), indica una pequeña distorsión entre la matriz de similitud y el espacio multidimensional en el dendrograma. El presente estudio constituye una importante contribución al conocimiento de la riqueza de helechos y licofitas presentes en los bosques semi-deciduos en el sur de Brasil.